AN ANALYSIS OF METAPHORS ON COVID-19 ISSUES IN ENGLISH NEWSPAPER - Suci Indah Faldias; Jismulatif Jismulatif; M. Syarfi M. Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research aims to identify and describe the types of metaphor used by journalist on COVID-19 issues in English newspaper and to find the dominant type of metaphor. This is a qualitative research with analysis method. The newspaper were used on this research are The Jakarta Post and China Daily. The newspaper during October 2020 were used and analyzed on COVID-9 issues only. There were 38 collected data from both newspapers. Structural metaphor appears 15 times, orientational metaphor appears 12 times, and ontological metaphor appears 11 times. Based on the research findings, it can be conclude that structural metaphor is the dominant type of metaphor that journalist used to write the news and their opinion in COVID-19 issues. It is suggested to the next researchers who are interested in metaphor need to more deepen analysis because news and data keep changing through times so that it can provide new results.Key Words: Metaphor, Metaphor in Newspaper, English Newspaper.